COMPARATIVE ETYMOLOGICAL STUDY OF ENGLISH AND PERSIAN COGNATE ROOT WORDS WITHIN THE INDO-EUROPEAN LANGUAGE FAMILY (SCIENCE TIME JOURNAL, 2026)
This article investigates the historical and etymological relationship between English and Persian through the comparative analysis of cognate root words inherited from the Proto-Indo-European language family. Although English belongs to the Germanic branch and Persian belongs to the IndoIranian branch, both languages preserve lexical similarities that demonstrate ancient linguisticconnections. The study focuses on lexical pairs such as warm–garm, eyebrow–ābru, bad–bad, right–rāst, kid–kudak, new–naw, star–sitora, dent–dandān, door–dar, and name–nām. Using comparative-historical,  semantic, and phonological methods, the research identifies patterns of sound transformation, lexical preservation, and semantic continuity. The findings reveal that English and Persian maintain traces of  common linguistic ancestry despite centuries of geographical and cultural divergence. The article contributes to comparative linguistics, historical philology, and Indo-European etymological studies.